Energy-water Nexus of Wastewater Treatment System: Conceptual Model and Framework. (December 2016) - Feng, Le; Chen, Bin
Abstract: Energy and water are two interwoven elements of wastewater treatment system (WWTS). Energy is consumed to remove pollutants in wastewater, decrease negative influence on the natural water environment, water is used to generate energy for system input. With the rapid increasing on wastewater quantity, how to improve wastewater treatment efficiency and reduce energy costs has attracted many attentions. However, there is lack of synthesize understanding of the energy-water nexus in WWTS. In this study, a new energy-water nexus conceptual framework is developed, energy used for wastewater extraction, operation of the wastewater treatment process and the waste recycling were explored. Efficiency and redundancy of the WWTS were also examined in structural nexus analysis based on Network Environ Analysis (NEA). The conceptual framework would help to investigate the mechanism and properties of the energy-water nexus for WWTS.